Logos and Prediction. Human Speech in Reasoning and Computation of Man-Machine Interaction. - Haase, Fee-Alexandra (Ostium, 2022)
This article examines the concept of prediction as a process of communication in the tradition of the humanities, especially philosophy and rhetoric, and contemporary computational applications of prediction in the digital environment with a focus on speech and the function of the voice. Despite showing that the historical path and contextualizing environment for the use of the concept is different in both areas, we argue that applications of this concept are related and present in the performance of reasoning and computation. The process of reasoning of the human mind has been treated in the humanities since antiquity. It is compared with the automated computational processes of machines using AI that result in predictions. We show and discuss the different conditions, means, and types of predictive methods and claim that in both cases the predictive outcome is limited to the previously given knowledge. But while purely computational prediction by AI is framed by its digital environment, prediction as the result of reasoning of the human mind can undergo modifications.